Boundary spanning design for better organisation / edited by Tarja Pääkkönen, Satu Miettinen. - Paakkonen, Tarja; Miettinen, Satu, 1972- (Edward Elgar Publishing, 2025)
This work explores the concept of boundary spanning design in different organisational fields, advocating for the awareness of human experience and the social aspects of design within an increasingly technology-oriented business landscape.